The Use of Interview as a Technique to Assess Students’ Speaking Skills of Senior High School - Sunny Naetipart; Zainul Aminin (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Speaking is a crucial component of communication. Speaking employed various tasks, expressing emotions or demands, requesting, and providing information. However, many students encounter challenges in speaking as a result of various difficulties. To address this, teachers can use interview techniques; interview techniques help to assess students' speaking skills to see and improve students' speaking skills. The objectives of this research are to explore the use of interview techniques to assess students' speaking skills and the difficulties and the benefits of using interview techniques. This research used basic interpretative qualitative research. This research was conducted on four English teachers in Surabaya, Indonesia, who had experienced an interview before. In collecting data, the researcher used interview and semi-interview guidelines. The findings indicate that the teachers used different types of interview techniques. The result showed interview technique can assess the students' speaking skills adapted to the teacher's need in English teaching. However, this technique also has difficulties and benefits that teacher and students may face. This study offers significant insights into teachers' perceptions and applications of interview techniques to assess students'' speaking skills. The findings of this research are anticipated to serve as a reference point and contribute pertinent data regarding teachers' experiences.